The genetic basis of hyaline fibromatosis syndrome in patients from a consanguineous background: a case series - Leila Youssefian; Hassan Vahidnezhad; Andrew Touati; Vahid Ziaee; Amir Hossein Saeidian; Sara Pajouhanfar; Sirous Zeinali; Jouni Uitto (BMC, 2018)
Abstract Background Hyaline fibromatosis syndrome (HFS) is a rare heritable multi-systemic disorder with significant dermatologic manifestations. It is caused by mutations in ANTXR2, which encodes a transmembrane receptor involved in collagen VI regulation in the extracellular matrix. Over 40 mutations in the ANTXR2 gene have been associated with cases of HFS. Variable severity of the disorder in different patients has been proposed to be related to the specific mutations in these patients and their location within the gene. Case presentation In this report, we describe four cases of HFS from consanguineous backgrounds. Genetic analysis identified a novel homozygous frameshift deletion c.969del (p.Ile323Metfs*14) in one case, the previously reported mutation c.134 T > C (p.Leu45Pro) in another case, and the recurrent homozygous frameshift mutation c.1073dup (p.Ala359Cysfs*13) in two cases. The epidemiology of this latter mutation is of particular interest, as it is a candidate for inhibition of nonsense-mediated mRNA decay. Haplotype analysis was performed to determine the origin of this mutation in this consanguineous cohort, which suggested that it may develop sporadically in different populations. Conclusions This information provides insights on genotype-phenotype correlations, identifies a previously unreported mutation in ANTXR2, and improves the understanding of a recurrent mutation in HFS.